Determinan Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - . Suparno (UNSIKA (Universitas Singaperbangsa Karawang), 2016)
This study is aimed to analyze and give empirical evidence that deviden policy, managerial ownership, and profitability, partially or simultaneously influence to companies value. Based on agency theory and deviden policy theory, this in line with phenomenon that manufacturing company’s increasing Indeks Harga Saham Gabungan (IHSG) still below average overall emitten’s IHSG. This research uses quantitative approach with 110 samples of manufacturing companies listed in Indonesian Stock Exchange (IDX) betweens 2009–2014. This research uses purposive sampling method. Data analyses technique use multiple linear regression. Result of this research show deviden policy significantly influence to companies value, while managerial ownership does’nt influence to companies value. However, companies value simultaniosly affected by all independent variable. This finding very interesting because the success of increasing companies value depend on capability of companies in empowering resources maximally, and depend on implementation of company’s policy. It is not because manager’s incentive.